A Systematic Review of Mobile Learning Trends in Supporting the Mastery of Spelling - Lau Yen Yen, Emily; Hashim, Harwati; Md Yunus, Melor (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Teaching and learning to spell forms the basis for mastering English Language. The emerging mobile learning trends in the current 21st century education is useful in teaching and learning spelling. However, there were limited reviews about them. As such, a systematic review was conducted to provide an up-to-date synthesis on the mobile learning trends in supporting the mastery of spelling from year 2012 to year 2022. This review adhered to Preferred Reporting Items for Systematic Reviews and Meta-Analyses which is also known as the PRISMA guideline. Three databases were involved: Web of Science, Scopus and Educational Resources Information Centre. After a rigorous screening process, a total of 19 articles fitted its objectives. Firstly, significant findings from the studies portrayed the use of four platforms in mobile learning trends in supporting the mastery of spelling namely mobile apps, spell-checker apps, word prediction apps and text messaging apps. Secondly, the primary level of education was more dominant in the related studies than the secondary and tertiary levels. Thirdly, it emphasised more on the students with a lower prevalence on teachers and both teachers and students as the respondents in the associated studies. This paper contributes to systematically reviewing 19 eligible related studies through a step-by-step protocol of identification, screening, eligibility and included as in the PRISMA guideline to establish quality review. It benefits both the English Language teachers and students in utilising various mobile learning platforms to support the mastery of spelling at all levels of education. It aspires to foreground the paucity in this topic in which more substantial studies are required to address the research gaps. The ultimate goal is to impose effective and practical strategies to advance mobile learning trends in supporting the mastery of spelling.